2013
DOI: 10.18553/jmcp.2013.19.7.523
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Why Some Community Pharmacists Do Not Provide 72-Hour Emergency Prescription Drugs to Medicaid Patients When Prior Authorization Is Not Available

Abstract: BACKGROUND: Existing federal law requires that a 72-hour emergency supply of a prescription drug be dispensed to Medicaid patients when prior authorization (PA) is not available and the medication is needed without delay. The pharmacist's role is to contact prescribers and inform them that PA is needed. If the prescriber cannot be reached, the pharmacist can dispense a 72-hour emergency supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In a study based on 401 pharmacists by George et al that evaluated cases of supplementary prescribing, prescribed medicines were used mostly for cardiovascular diseases [17]. One American study indicated that 75% of pharmacists only fill emergency prescriptions several times a month and that they may dispense antibiotics, inhaled medications, antidiabetic medicines, and drugs used for nausea and vomiting [22]. Our own data analysis indicated that the most common prescriptions were for cardiovascular medicines and anti-infectives.…”
Section: Discussionmentioning
confidence: 74%
“…In a study based on 401 pharmacists by George et al that evaluated cases of supplementary prescribing, prescribed medicines were used mostly for cardiovascular diseases [17]. One American study indicated that 75% of pharmacists only fill emergency prescriptions several times a month and that they may dispense antibiotics, inhaled medications, antidiabetic medicines, and drugs used for nausea and vomiting [22]. Our own data analysis indicated that the most common prescriptions were for cardiovascular medicines and anti-infectives.…”
Section: Discussionmentioning
confidence: 74%
“…These studies reported the characteristics of patients who received a tider4,5, the tider medications dispensed4,5, and patients’ and pharmacists’ perceptions of tiders on medication adherence 6,7. These studies had either small sample sizes or were focused on the legal implications of providing a tider 4,5,6,7. Studies detailing the cost of tider medication dispensing and contrasting the characteristics of tider and non-tider patients and medications have not been reported.…”
Section: Introductionmentioning
confidence: 99%